Cultural enrichment in Indonesian language for foreign speaker (BIPA) learning with Trihita Karana concept - Adnyana, Ida Bagus Artha; Rahmanu, I Wayan Eka Dian; Sutarma, I Gusti Putu; Handayani, Luh Nyoman Chandra (Politeknik Negeri Bali, 2021)
Indonesian Language for foreign speaker (BIPA) students are very interested in cultural values, the provision of cultural values ​​is very important for BIPA students to enrich their language skills. Even cultural errors can be more serious than language errors. Trihita Karana is a philosophical value of living in harmony with God, nature, and fellow human beings. To teach BIPA students, it is necessary to have a genuine learning method so that BIPA students can absorb the culture significantly. The twenty BIPA learners in the State Polytechnic of Bali were conducted in this research. Questionnaire and observation methods were used in data collection. The data obtained were then analysed using a qualitative descriptive method. Based on the results of BIPA students' responses to several methods being tested, it can be concluded that 96.7% of respondents argued that the Trihita Karana cultural learning method was very feasible to support the BIPA learning process. There were several methods appreciated by BIPA students, including guessing pictures, running while dictation, observing, video documentation, immersion, and debate. Among these methods, the immersion method was the most favoured by BIPA students because they directly experienced it in daily life.